Factors Affecting Family Physicians' Drug Prescribing: A Cross-Sectional Study in Khuzestan, Iran - Mohammad Arab; Amin Torabi Pour; Abbas Rahimifrooshani; Arash Rashidian; Nayeb Fadai; Rohollah Asqari (Kerman University of Medical Sciences, 2014)
Background Rational prescription is a considerable issue which must be paid more attention to assess the behavior of prescribers. The aim of this study was to examine factors affecting family physicians' drug prescribing. Methods We carried out a retrospective cross-sectional study in Khuzestan province, Iran in 2011. Nine hundred eighty-six prescriptions of 421 family physicians (including 324 urban and 97 rural family physicians) were selected randomly. A multivariate Poisson regression was used to investigate potential determinants of the number of prescribed drug per patient. Results The mean of medication per patient was 2.6 ± 1.2 items. In the majority (91.9%) of visits a drugs was prescribed. The most frequent dosage forms were tablets, syrups and injection in 30.1%, 26.9%, and 18.7% of cases respectively. Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) and antibiotics were 29.7% and 17.1% of prescribed drugs respectively. The tablets were the most frequent dosage forms (38.6% of cases) in adult's patients and syrups were the most frequent dosage forms (49% of cases) in less than 18 years old. Paracetamols were popular form of NSAIDs in two patients groups. The most common prescribed medications were oral form. Conclusion In Khuzestan, the mean of medication per patient was fewer than national average. Approximately, pattern of prescribed drug by family physicians (including dosage form and type of drugs) was similar to other provinces of Iran.